Measurements of debris flow entrainment and dynamics - Vicari Hervé; Ng Charles W. W.; Nordal Steinar; Thakur Vikas; De Silva W. A. Roanga K.; Liu Haiming; Choi Clarence E. (E3S Web of Conferences, 2023)
The mechanisms of debris flows and their interaction with mitigation structures are still not well understood. Among the research challenges, only few entrainment measurements are available in literature, as entrainment is often masked by deposition on top. In this paper, we present a simple, cheap, and effective method to measure the entrainment depths. Flume experiments have therefore been performed to assess the influence of the initial debris flow volume and of an upstream flexible barrier on entrainment. To better understand the debris flow dynamics, the flow basal stresses have been measured. A high degree of liquefaction at the base of the debris flow is observed. A mitigation measure to reduce entrainment has also been studied. A compact flexible barrier was installed in the upstream part of the channel and is observed to deflect the flow along a curvilinear path. High normal stresses are measured at the base of the overflow, which are caused by the additional centrifugal stresses from the overflow. The results from the flume tests suggest that the flow interaction with an upstream flexible barrier may significantly influence the debris flow dynamics both upstream and downstream of the barrier.